Influence of DRD2 Polymorphisms on the Clinical Outcomes of Opioiddependent Patients on Methadone Maintenance Therapy - Zahari, Zalina (J Pharm Bioallied Sci, 2020)
INTRODUCTION: Dopamine receptor D2 (DRD2) is one of the dopamine receptors that have been studied in relation to opioid dependence. It is possible, therefore, that DRD2 gene (DRD2) polymorphisms influence treatment outcomes of patients with opioid dependence. The objective of this study was to investigate the influence of DRD2 polymorphisms on the clinical outcomes of opioid-dependent patients on methadone maintenance therapy (MMT). MATERIALS AND METHODS: Patients with opioid dependence (n = 148) were recruited from MMT clinics. Pain sensitivity, severity of the opiate withdrawal syndrome, and sleep quality were assessed using cold pressor test (CPT), Subjective Opiate Withdrawal Scale (SOWS-M), and Pittsburgh Sleep Quality Index (PSQI)-Malay, respectively. Deoxyribonucleic acid (DNA) was extracted from whole blood, and then was used for genotyping of Val96Ala, Leu141Leu, Val154Ile, Pro310Ser, Ser311Cys, TaqI A, -141C Ins/Del, and A-241G polymorphisms. RESULTS: Among 148 patients, 8.1% (n = 12), 60.8% (n = 90), 27.7% (n = 41), and 29.1% (n = 43) had at least one risk allele for Ser311Cys, TaqI A, -141C Ins/Del, and A-241G polymorphisms, respectively. There were no significant differences in pain responses (pain threshold, tolerance, and intensity), SOWS, and PSQI scores between DRD2 polymorphisms. CONCLUSION: The common DRD2 polymorphisms are not associated with pain sensitivity, severity of the opiate withdrawal syndrome, and sleep quality in patients with opioid dependence on MMT. However, this may be unique for Malays. Additional research should focus on investigating these findings in larger samples and different ethnicity.